Genetics and marker-assisted breeding for sex expression in cucumber - R. K. Dhall; Harleen Kaur; Pooja Manchanda; Eshanee (Frontiers in Genetics, 2023)
Cucumber is an important vegetable crop that provides an accessible draft genome, which has significantly expedited research in various fields of molecular genetics. Cucumber breeders have been employing various methodologies to improve the yield and quality of the crop. These methodologies comprise enhancement of disease resistance, use of gynoecious sex types and their association with parthenocarpy, alterations in plant architecture, and enhancement of genetic variability. The genetics of sex expression are a complex trait in cucumbers but are very significant for the genetic improvement of cucumber crop. This review comprises an explanation of the current status of gene(s) involvement and its expression studies, the inheritance of genes, molecular markers, and genetic engineering associated with sex determination, as well as a discussion of the role of ethylene in sex expression and sex-determining genes of the ACS family. There is no doubt that gynoecy is an important trait among all sex forms of cucumber for heterosis breeding, but if it is associated with parthenocarpy, fruit yield can be enhanced to a greater extent under favorable conditions. However, little information is available with regard to parthenocarpy in gynoecious-type cucumber. This review sheds light on the genetics and molecular mapping of sex expression and could be beneficial especially to cucumber breeders and other scientists working on crop improvement via traditional and molecular assistant approaches.